Water-based self-adhesive insulating paint for silicon steel and preparation method thereof

The aqueous self-adhesive insulating coating prepared by chemical modification combined with modified epoxy resin and nanoparticles solves the problem of insufficient bonding strength of thin silicon steel sheets, and achieves efficient and stable insulation and mechanical strength improvement.

CN119463628AInactive Publication Date: 2025-02-18SHANGHAI FENGYE CHEM CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411595915.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-11
Publication Date
2025-02-18
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

When processing increasingly thinner silicon steel sheets, the bonding strength is insufficient, making it difficult to maintain the shape and mechanical strength of the iron core, and the production efficiency is low, making the bonding condition difficult to control.

Method used

Using water-based self-adhesive insulating coatings, acrylate emulsions are prepared by chemical modification to make them cationic charges, and combined with modified epoxy resin and modified nanoparticles, it is prepared with high bond strength, chemical corrosion resistance and Self-adhesive coating with good adhesion.

Benefits of technology

The self-adhesion effect of high bond strength is achieved, and no additional adhesive is required, and the stable insulation performance can be maintained at higher working temperatures, which improves the insulation performance of silicon steel sheets and the mechanical strength of the iron core.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119463628A_ABST
    Figure CN119463628A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of metal surface treatment, and particularly relates to a water-based self-adhesive insulating coating for silicon steel and a preparation method of the water-based self-adhesive insulating coating. On one hand, the acrylate emulsion is prepared through a chemical modification means, so that the acrylate emulsion has cationic charges; and the effect of effective interaction with the negatively charged surface is enhanced. On the other hand, the self-adhesive insulating paint prepared from the modified acrylate emulsion and the modified epoxy resin has good chemical corrosion resistance, hydrolysis resistance, chemical resistance, flexibility and adhesive force. The silicon steel sheet adhesive is applied to the surface of a silicon steel sheet, aims to improve the insulating property of the silicon steel sheet and reduce iron loss, has self-adhesion, and can achieve a good adhesion effect without an additional adhesive.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of metal surface treatment, and relates to a water-based self-adhesive insulating coating for silicon steel, and in particular to a water-based self-adhesive insulating coating for silicon steel and a preparation method thereof. Background Art

[0002] Water-based self-adhesive insulating coating for silicon steel is a coating specially designed for coating the surface of silicon steel sheets, aiming to improve the insulation performance and mechanical strength of electromagnetic equipment such as motors and transformers. Silicon steel is a special steel material, mainly used to make iron cores in electrical equipment such as transformers, motors, generators, etc. Silicon steel is widely used in these fields because of its following characteristics: High magnetic permeability: Silicon steel has good magnetic conductivity, which means that it can produce a large magnetic induction intensity in the energized coil, thus helping to reduce the size of equipment such as transformers. Low hysteresis loss: Hysteresis loss refers to the energy consumed by the material due to hysteresis during the magnetization process. Silicon steel has a narrow hysteresis loop, which means that it consumes less energy during magnetization and demagnetization, and therefore generates less heat. Low eddy current loss: Eddy current loss refers to the energy loss caused by the induced current (eddy current) generated inside the iron core under the action of the alternating magnetic field. Silicon steel sheets are stacked in a way that they are insulated from each other, which can significantly reduce the path length of the eddy current, thereby reducing eddy current losses. Good processing performance: Silicon steel sheets are usually processed into thin sheets, which are convenient for stamping, cutting and other processing, so that they can be made into iron cores of different shapes and sizes as needed. Silicon steel is an iron-silicon alloy with a silicon content usually between 0.5% and 4.8%, and a very low carbon content, usually less than 0.08%. It can be divided into two categories according to its magnetic properties: non-directional silicon steel and oriented silicon steel. Non-directional silicon steel is suitable for occasions where uniform magnetism is required in all directions; oriented silicon steel has better magnetism and is particularly suitable for manufacturing transformer cores. Most silicon steel sheets are produced through cold rolling, which can achieve better magnetic properties. The production process of silicon steel is relatively complex and requires strict manufacturing technology. In short, silicon steel plays a vital role in electrical equipment due to its excellent magnetic properties and low loss characteristics.

[0003] In order to reduce the heating caused by the induced current of the large iron core, silicon steel is now prepared into silicon steel sheets, coated with insulating coatings on both sides, and then these silicon steel sheets are stamped and shaped, stacked, and then connected into iron cores by welding, locking or riveting. In recent years, in order to save energy, especially to meet the requirements of high torque, high speed and high efficiency of new energy vehicle motors, and to reduce the eddy current loss of the iron core, the silicon steel sheets of new energy vehicle motors have become thinner and thinner, even as thin as 0.2 and 0.15 mm. The thinner the silicon steel sheets, the more difficult it is to rivet and weld, and the end faces of the stacked layers are easy to separate, making it difficult to maintain the shape of the iron core. Therefore, after stacking thinner and thinner silicon steel sheets, the method of bonding them by surface fixing has become an effective method to improve the fastening strength of the iron core. If an adhesive is applied to each punched and sheared silicon steel sheet, the production efficiency of this method is very low, and there are also problems such as difficult to control and uneven bonding conditions. The self-adhesive coating is applied to the surface of the continuously running steel plate by roller coating or spraying, and then enters the drying furnace and is heated by open flame or hot air for a certain period of time to form a self-adhesive coating. The self-adhesive coating has the characteristics of high insulation strength, good corrosion resistance, good punching property and high bonding strength. The electrical steel plate coated with the self-adhesive coating can be stored for a long time in sheet or roll form. During the storage at room temperature, the silicon steel sheet will not corrode and rust, nor will it cause problems such as coating adhesion. After that, the sheet is cut and punched according to the requirements of the motor core to form a silicon steel sheet of a certain shape. Multiple silicon steel sheets are stacked up, fixed by clamps, placed in an oven at a certain temperature, and after curing for a certain period of time, the self-adhesive coating between the silicon steel sheets is bonded into one under the action of pressure and temperature, so that an iron core with good mechanical strength and rigidity can be formed.

[0004] In order to meet the market demand, the present invention provides a water-based self-adhesive insulating coating for silicon steel. On the one hand, an acrylic emulsion is prepared by chemical modification to make it have a cationic charge. The effect of effective interaction with the negatively charged surface is enhanced. On the other hand, the self-adhesive insulating coating prepared by the present invention using modified acrylic emulsion and modified epoxy resin has good chemical corrosion resistance, hydrolysis resistance, chemical resistance, flexibility and adhesion. It is used on the surface of silicon steel sheets to improve the insulation performance of silicon steel sheets and reduce iron loss. At the same time, it has self-adhesiveness and can achieve good bonding effect without additional adhesives. Summary of the invention

[0005] In view of the deficiencies of the prior art, the purpose of the present invention is to prepare a self-adhesive coating with high bonding strength. At the same time, the coating is a water-based self-adhesive coating, which is green and environmentally friendly and has high construction safety. The present invention is achieved by: a water-based self-adhesive insulating coating for silicon steel and a preparation method thereof, which specifically comprises the following steps:

[0006] S1. Soak 20-42g of melamine in 50mL of concentrated nitric acid and 20mL of concentrated sulfuric acid at a temperature of 55-60°C. After soaking for 10-17h, wash with deionized water to obtain a white tubular sample. Mix the white powder sample and 2-3g of boric acid evenly, place in a vacuum tube furnace, and vacuum calcine for 2-3h at a vacuum calcination temperature of 680-750°C. After vacuum carbonization, the white powder becomes a black tubular powder, which is a boron-doped carbon fiber material. Place the carbon fiber material in an acetone solution of γ-aminopropyltriethoxysilane (KH550), wherein the mass fraction of γ-aminopropyltriethoxysilane is 0.5-2.0wt%. After ultrasonic treatment for 30min, centrifugal drying is performed to obtain a modified boron-doped carbon fiber. The introduction of boron in this step greatly improves the electronic structure of the carbon fiber surface, which is conducive to better dispersion of the carbon fiber in the coating. In addition, in this step, after the modified boron-doped carbon fiber is immersed in an acetone solution of γ-aminopropyltriethoxysilane (KH550), it can ensure that the carbon fiber is better immersed in the mixed resin system, thereby ensuring that the carbon fiber is fully impregnated.

[0007] S2, preparation of modified epoxy resin emulsion: weigh 80-120g of bisphenol A epoxy resin of model 6828 into a beaker, start stirring at a stirring speed of 2000-3000rpm, and heat to a temperature of 55-66°C; after keeping warm for 10-15min, add 12-15g of modified boron-doped carbon fiber prepared in step S1 and 8-11g of hexadecyltrimethylammonium bromide (CTAB), and continue stirring for 22-30min; then drop 150-230g of deionized water into the beaker at a speed of 3-5g / min, and adjust the speed of the high-speed disperser to 5000rpm; after the dropwise addition is completed, reduce the dispersion speed to 2000rpm, keep the temperature at 65°C, keep warm for 1-2h, then stir for 30min, cool to room temperature, filter and discharge, and obtain epoxy resin emulsion. In this step, hexadecyl trimethyl ammonium bromide (CTAB) is a cationic emulsifier that can form stable micelles in aqueous solution and has good bactericidal properties. The interfacial adhesion between carbon fiber and polymer matrix plays a vital role in controlling the overall performance of the composite material. The interfacial adhesion of the modified boron-doped carbon fiber used in this step increases the structural integrity of the composite material and effectively transfers stress from the fiber to the matrix. The toughness of the coating is effectively improved by epoxy resin and modified boron-doped carbon fiber in this step.

[0008] S3, add 3-5g of aluminum nitrate, 4-6g of silicon dioxide and 1.5g of hexadecyltrimethylammonium bromide into a 100mL reactor, then add 60mL of acetonitrile, react in a muffle furnace for 12-18h, the reaction temperature is 180-220℃; after cooling to room temperature, centrifugal drying is performed to obtain black powder; the black powder is placed in a tubular furnace, in an Ar gas atmosphere, the reaction temperature is controlled at 550-680℃, and vacuum calcined for 2-3h to obtain modified nanoparticles. In this step, the acetonitrile solution is used to promote the coating of the carbon layer outside the silicon-aluminum nanoparticles, and the modified silicon-aluminum nanoparticles are obtained by vacuum calcination.

[0009] S4, prepare modified acrylic emulsion: 80-130g of octadecyl acrylate, 5-13g of acrylate-based silicone monomer, 3-5g of benzalkonium chloride (BAC), 2-3g of modified nanoparticles prepared in step S3, 30-50mL of propylene glycol, 60-80mL of deionized water and 15-30mL of glacial acetic acid are prepared and reacted in a constant temperature water bath for 50-80min, and the temperature is controlled at 60°C; then, after stirring at 5000rpm for 20-30min, a pre-emulsion is obtained; the pre-emulsion is transferred to a closed reactor, and n-dodecyl mercaptan and 2,2'-azobisisobutylamidine dihydrochloride are added, and nitrogen replacement is performed. Subsequently, the reaction is kept at 60°C for 5-8h under continuous stirring and nitrogen protection. After the reaction is completed, it is cooled to room temperature and filtered to obtain a modified acrylic emulsion. In this step, the mechanical strength and durability of the acrylic emulsion are improved by adding modified nanoparticles.

[0010] S5. Preparation of self-bonding coating: 110-150 g of the modified epoxy resin emulsion prepared in step S2, 90-115 g of the modified acrylate emulsion prepared in step S4, and 5-8 g of polyethylene glycol ether are uniformly mixed, and stirred at a speed of 3000 rpm for 40-60 min to obtain a water-based self-bonding insulating coating for silicon steel.

[0011] Preferably: the bisphenol A epoxy resin of model 6828 described in the present invention is purchased from Foshan Nanhai Huangqi Chemical Glass Co., Ltd.

[0012] Preferably: the chemical reagents used in the steps of the present invention are all purchased from Shanghai Aladdin Reagent Co., Ltd.

[0013] Due to the adoption of the above technical solution, the technical progress achieved by the present invention is:

[0014] 1. The water-based self-adhesive insulating coating for silicon steel prepared by the present invention uses water as the main solvent, reduces the emission of harmful volatile organic compounds, and is more environmentally friendly.

[0015] 2. The water-based self-adhesive insulating coating for silicon steel prepared by the present invention does not require additional adhesives, and the coating itself has sufficient adhesive force to form a firm insulating layer during the heating process.

[0016] 3. The water-based self-adhesive insulating coating for silicon steel prepared by the present invention can maintain stable insulating properties at higher operating temperatures.

[0017] 4. The water-based self-adhesive insulating coating for silicon steel prepared by the present invention has good resistance to common industrial chemicals.

[0018] 5. The water-based self-adhesive insulating coating for silicon steel prepared by the present invention can provide a good electrical isolation effect and prevent current leakage.

[0019] 6. The water-based self-adhesive insulating coating for silicon steel prepared by the present invention forms a hard protective layer after the coating is dried, which helps to improve the bending resistance of the silicon steel sheet.

[0020] 7. The preparation method of the present invention is simple, low-cost, and can be adapted to industrial production.

[0021] 8. The modified acrylic emulsion prepared by chemical modification in the present invention has a cationic charge. On the other hand, the self-adhesive insulating coating prepared by the present invention using the modified acrylic emulsion and the modified epoxy resin has good chemical corrosion resistance. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 This is a SEM image of a white tubular sample obtained after treating melamine in Example 1 of the present invention;

[0023] Figure 2 This is a SEM image of a white powder sample obtained after treating melamine in Comparative Example 1 of the present invention;

[0024] Figure 3 This is a SEM image of a white tubular sample obtained after treating melamine in Comparative Example 2 of the present invention;

[0025] Figure 4 This is a SEM image of the boron-doped carbon fiber material prepared in Example 2 of the present invention.

[0026] Figure 5 This is an SEM image of the boron-doped carbon fiber material prepared in Comparative Example 3 of the present invention.

[0027] Figure 6 This is a TEM image of the boron-doped carbon fiber material prepared in Example 3 of the present invention. DETAILED DESCRIPTION

[0028] The following describes the embodiments of the present invention by specific examples, and those skilled in the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification. The present invention can also be implemented or applied through other different specific embodiments, and the details in this specification can also be modified or changed in various ways based on different viewpoints and applications without departing from the spirit of the present invention. It should be noted that the following embodiments and features in the embodiments can be combined with each other without conflict.

[0029] Example 1

[0030] S1. Soak 20g of melamine in 50mL of concentrated nitric acid and 20mL of concentrated sulfuric acid at 55°C. After soaking for 10h, wash with deionized water to obtain a white tubular sample. Mix the white powder sample and 2g of boric acid evenly, place in a vacuum tube furnace, and vacuum calcine for 2h at a temperature of 680°C. After vacuum carbonization, the white powder becomes a black tubular powder, which is a boron-doped carbon fiber material. Place the carbon fiber material in an acetone solution of γ-aminopropyltriethoxysilane (KH550) with a mass fraction of 0.5wt%. After ultrasonic treatment for 30min, centrifugal drying is performed to obtain a modified boron-doped carbon fiber. The introduction of boron in this step greatly improves the electronic structure of the carbon fiber surface, which is conducive to better dispersion of the carbon fiber in the coating. In addition, in this step, after the modified boron-doped carbon fiber is immersed in an acetone solution of γ-aminopropyltriethoxysilane (KH550), it can ensure that the carbon fiber is better immersed in the mixed resin system, thereby ensuring that the carbon fiber is fully impregnated.

[0031] S2, preparation of modified epoxy resin emulsion: weigh 80g of bisphenol A epoxy resin of model 6828 in a beaker, start stirring, stirring speed is 2000rpm, and heat to 55℃; after keeping warm for 10min, add 12g of modified boron-doped carbon fiber prepared in step S1 and 8g of hexadecyltrimethylammonium bromide (CTAB), and continue stirring for 22min; then drip 150g of deionized water into the beaker at a speed of 3g / min, and adjust the speed of the high-speed disperser to 5000rpm; after the dropwise addition is completed, reduce the dispersion speed to 2000rpm, keep the temperature at 65℃, keep warm for 1h, then stir for 30min, cool to room temperature, filter and discharge, and obtain epoxy resin emulsion. Hexadecyltrimethylammonium bromide (CTAB) in this step is a cationic emulsifier, which can form stable micelles in aqueous solution and has good bactericidal properties. The interfacial adhesion between carbon fiber and polymer matrix plays a vital role in controlling the overall performance of composite materials. The interfacial adhesion of the modified boron-doped carbon fibers used in this step increases the structural integrity of the composite material and effectively transfers stress from the fibers to the matrix. The toughness of the coating is effectively improved by the epoxy resin and the modified boron-doped carbon fibers in this step.

[0032] S3, add 3g of aluminum nitrate, 4g of silicon dioxide and 1.5g of hexadecyltrimethylammonium bromide into a 100mL reactor, then add 60mL of acetonitrile, react in a muffle furnace for 12h, the reaction temperature is 180°C; cool to room temperature and centrifuge to obtain black powder; place the black powder in a tubular furnace, in an Ar gas atmosphere, the reaction temperature is controlled at 550°C, and vacuum calcined for 2h to obtain modified nanoparticles. In this step, the acetonitrile solution is used to promote the coating of the carbon layer outside the silicon-aluminum nanoparticles, and the modified silicon-aluminum nanoparticles are obtained by vacuum calcination.

[0033] S4, prepare modified acrylic emulsion: 80g of octadecyl acrylate, 5g of acrylate-based silicone monomer, 3g of benzalkonium chloride (BAC), 2g of modified nanoparticles prepared in step S3, 30mL of propylene glycol, 60mL of deionized water and 15mL of glacial acetic acid are prepared and reacted in a constant temperature water bath for 50min, and the temperature is controlled at 60°C; then, after stirring at 5000rpm for 20min, a pre-emulsion is obtained; the pre-emulsion is transferred to a closed reactor, and n-dodecyl mercaptan and 2,2'-azobisisobutylamidine dihydrochloride are added, and nitrogen replacement is performed. Subsequently, the reaction is kept at 60°C for 5h under continuous stirring and nitrogen protection. After the reaction is completed, it is cooled to room temperature and filtered to obtain modified acrylic ester. In this step, the mechanical strength and durability of the acrylic emulsion are improved by adding modified nanoparticles.

[0034] S5. Preparation of self-bonding coating: 110 g of the modified epoxy resin emulsion prepared in step S2, 90 g of the modified acrylate emulsion prepared in step S4, and 5 g of polyethylene glycol ether are uniformly mixed, and stirred at a speed of 3000 rpm for 40 minutes to obtain a water-based self-bonding insulating coating for silicon steel.

[0035] Comparative Example 1: Except that 50 mL of concentrated nitric acid and 20 mL of concentrated sulfuric acid are replaced by 70 mL of concentrated sulfuric acid in step S1, the remaining steps are the same as those in Example 1.

[0036] Comparative Example 2: Except that 50 mL of concentrated nitric acid and 20 mL of concentrated sulfuric acid are replaced by 70 mL of concentrated nitric acid in step S1, the remaining steps are the same as those in Example 1.

[0037] Figure 1 This is a SEM image of a white tubular sample obtained after treating melamine in Example 1 of the present invention; Figure 2 This is a SEM image of a white powder sample obtained after treating melamine in Comparative Example 1 of the present invention; Figure 3 This is a SEM image of a white tubular sample obtained after treating melamine in comparative example 2 of the present invention. In an acid solution, melamine will be partially hydrolyzed to form cyanuric acid, and then melamine can interact with the newly generated cyanuric acid to form a supramolecular intermediate in situ. Studies have shown that in the process of forming supramolecular intermediates, the melamine-cyanuric acid molecules in the plane can be interconnected by intermolecular hydrogen bonds, while the triazine rings in adjacent interlayers grow in a vertical direction through -π covalent bonds. As the reaction temperature increases, a supramolecular precursor with the desired structure and morphology can be obtained by stabilizing the intermolecular hydrogen bonds. Therefore, the acid ratio and the water area temperature are very important for the formation of a stable supramolecular rod-like structure. From Figure 1 and Figure 3 By comparison, it can be seen that the diameter of the tubular material after being processed in Example 1 of the present invention is thinner. Figure 2 The prepared white powder basically does not form a tubular structure. It can be seen that in the present invention, it is necessary to soak melamine in concentrated nitric acid and concentrated sulfuric acid in a suitable volume ratio to obtain a tubular precursor. The white tubular sample powder prepared by the present invention has a relatively large diameter and can be better mixed with boric acid, and modified boron-doped carbon fibers can be successfully prepared after subsequent carbonization.

[0038] Example 2

[0039] S1. Soak 42g of melamine in 50mL of concentrated nitric acid and 20mL of concentrated sulfuric acid at 60°C. After soaking for 17h, wash with deionized water to obtain a white tubular sample. Mix the white powder sample and 3g of boric acid evenly, place it in a vacuum tube furnace, and vacuum calcine for 3h at a vacuum calcination temperature of 750°C. After vacuum carbonization, the white powder becomes a black tubular powder, which is a boron-doped carbon fiber material. Place the carbon fiber material in an acetone solution of γ-aminopropyltriethoxysilane (KH550) with a mass fraction of 2.0wt%. After ultrasonic treatment for 30min, centrifugal drying is performed to obtain a modified boron-doped carbon fiber. The introduction of boron in this step greatly improves the electronic structure of the carbon fiber surface, which is conducive to better dispersion of the carbon fiber in the coating. In addition, in this step, after the modified boron-doped carbon fiber is immersed in an acetone solution of γ-aminopropyltriethoxysilane (KH550), it can ensure that the carbon fiber is better immersed in the mixed resin system, thereby ensuring that the carbon fiber is fully impregnated.

[0040] S2, preparation of modified epoxy resin emulsion: weigh 120g of bisphenol A epoxy resin of model 6828 in a beaker, start stirring, stirring speed is 3000rpm, warm to 66℃; add 15g of modified boron-doped carbon fiber prepared in step S1 and 11g of hexadecyltrimethylammonium bromide (CTAB) after keeping warm for 15min, continue stirring for 30min; then drip 230g of deionized water into the beaker at a speed of 5g / min, and adjust the speed of the high-speed disperser to 5000rpm; after the dropwise addition is completed, reduce the dispersion speed to 2000rpm, keep the temperature at 65℃, keep warm for 2h, then stir for 30min, cool to room temperature, filter and discharge, and obtain epoxy resin emulsion. Hexadecyltrimethylammonium bromide (CTAB) in this step is a cationic emulsifier, which can form stable micelles in aqueous solution and has good bactericidal properties. The interfacial adhesion between carbon fiber and polymer matrix plays a vital role in controlling the overall performance of the composite material. The interfacial adhesion of the modified boron-doped carbon fiber used in this step increases the structural integrity of the composite material and effectively transfers stress from the fiber to the matrix. The toughness of the coating is effectively improved by the epoxy resin and the modified boron-doped carbon fiber in this step.

[0041] S3, take 5g of aluminum nitrate, 6g of silicon dioxide and 1.5g of hexadecyltrimethylammonium bromide and add them to a 100mL reactor, then add 60mL of acetonitrile, react in a muffle furnace for 18h, the reaction temperature is 220℃; after cooling to room temperature, centrifuge and dry to obtain black powder; place the black powder in a tubular furnace, in an Ar gas atmosphere, the reaction temperature is controlled at 680℃, and vacuum calcined for 3h to obtain modified nanoparticles. In this step, the acetonitrile solution is used to promote the coating of the carbon layer outside the silicon-aluminum nanoparticles, and the modified silicon-aluminum nanoparticles are obtained by vacuum calcination.

[0042] S4, prepare modified acrylic emulsion: 130g of octadecyl acrylate, 13g of acrylate-based silicone monomer, 5g of benzalkonium chloride (BAC), 3g of modified nanoparticles prepared in step S3, 50mL of propylene glycol, 80mL of deionized water and 30mL of glacial acetic acid are prepared and reacted in a constant temperature water bath for 80min, and the temperature is controlled at 60°C; then, after stirring at 5000rpm for 30min, a pre-emulsion is obtained; the pre-emulsion is transferred to a closed reactor, and n-dodecyl mercaptan and 2,2'-azobisisobutylamidine dihydrochloride are added, and nitrogen replacement is performed. Subsequently, the reaction is kept at 60°C for 5-8h under continuous stirring and nitrogen protection. After the reaction is completed, it is cooled to room temperature and filtered to obtain modified acrylic ester. In this step, the mechanical strength and durability of the acrylic emulsion are improved by adding modified nanoparticles.

[0043] S5. Preparation of self-bonding coating: 150 g of the modified epoxy resin emulsion prepared in step S2, 115 g of the modified acrylate emulsion prepared in step S4, and 8 g of polyethylene glycol ether are uniformly mixed, and stirred at a speed of 3000 rpm for 60 min to obtain a water-based self-bonding insulating coating for silicon steel.

[0044] Comparative Example 3: Except that 3 g of boric acid is not added in step S1, the remaining steps are the same as those in Example 2.

[0045] Figure 4 This is a SEM image of the boron-doped carbon fiber material prepared in Example 2 of the present invention. Figure 5 This is a SEM image of the carbon fiber material prepared in Comparative Example 3 of the present invention. Figure 4 and Figure 5 By comparison, it can be seen that there are some differences in morphology between the two. The introduction of boron in this step greatly improves the electronic structure of the carbon fiber surface, which is conducive to better dispersion of the carbon fiber in the coating, thereby promoting the growth of many small tubes on the surface of the carbon fiber material, which is conducive to soaking the modified boron-doped carbon fiber in the acetone solution of γ-aminopropyltriethoxysilane (KH550), which can ensure that the carbon fiber is better immersed in the mixed resin system, thereby ensuring that the carbon fiber is fully impregnated.

[0046] Example 3

[0047] S1. Soak 39g of melamine in 50mL of concentrated nitric acid and 20mL of concentrated sulfuric acid at 56°C. After soaking for 17h, wash with deionized water to obtain a white tubular sample. Mix the white powder sample and 3g of boric acid evenly, place in a vacuum tube furnace, and vacuum calcine for 3h at a temperature of 730°C. After vacuum carbonization, the white powder becomes a black tubular powder, which is a boron-doped carbon fiber material. Place the carbon fiber material in an acetone solution of γ-aminopropyltriethoxysilane (KH550) with a mass fraction of 2.0wt%. After ultrasonic treatment for 30min, centrifugal drying is performed to obtain a modified boron-doped carbon fiber. The introduction of boron in this step greatly improves the electronic structure of the carbon fiber surface, which is conducive to better dispersion of the carbon fiber in the coating. In addition, in this step, after the modified boron-doped carbon fiber is immersed in an acetone solution of γ-aminopropyltriethoxysilane (KH550), it can ensure that the carbon fiber is better immersed in the mixed resin system, thereby ensuring that the carbon fiber is fully impregnated.

[0048] S2, preparation of modified epoxy resin emulsion: weigh 115g of bisphenol A epoxy resin of model 6828 in a beaker, start stirring, stirring speed is 3000rpm, warm to 66°C; after keeping warm for 15min, add 15g of modified boron-doped carbon fiber prepared in step S1 and 11g of hexadecyltrimethylammonium bromide (CTAB), continue stirring for 22-30min; then drip 230g of deionized water into the beaker at a speed of 5g / min, and adjust the speed of the high-speed disperser to 5000rpm; after the dropwise addition is completed, reduce the dispersion speed to 2000rpm, keep the temperature at 65°C, keep warm for 2h, then stir for 30min, cool to room temperature, filter and discharge, and obtain epoxy resin emulsion. In this step, hexadecyltrimethylammonium bromide (CTAB) is a cationic emulsifier, which can form stable micelles in aqueous solution and has good bactericidal properties. The interfacial adhesion between carbon fiber and polymer matrix plays a vital role in controlling the overall performance of the composite material. The interfacial adhesion of the modified boron-doped carbon fiber used in this step increases the structural integrity of the composite material and effectively transfers stress from the fiber to the matrix. The toughness of the coating is effectively improved by the epoxy resin and the modified boron-doped carbon fiber in this step.

[0049] S3, take 5g of aluminum nitrate, 6g of silicon dioxide and 1.5g of hexadecyltrimethylammonium bromide and add them to a 100mL reactor, then add 60mL of acetonitrile, react in a muffle furnace for 12-18h, the reaction temperature is 220℃; after cooling to room temperature, centrifuge and dry to obtain black powder; place the black powder in a tubular furnace, in an Ar gas atmosphere, the reaction temperature is controlled at 680℃, and vacuum calcined for 2-3h to obtain modified nanoparticles. In this step, the acetonitrile solution is used to promote the coating of the carbon layer outside the silicon-aluminum nanoparticles, and the modified silicon-aluminum nanoparticles are obtained by vacuum calcination.

[0050] S4, prepare modified acrylic emulsion: 130g of octadecyl acrylate, 13g of acrylate-based silicone monomer, 5g of benzalkonium chloride (BAC), 3g of modified nanoparticles prepared in step S3, 50mL of propylene glycol, 80mL of deionized water and 30mL of glacial acetic acid are prepared and reacted in a constant temperature water bath for 80min, and the temperature is controlled at 60°C; then, after stirring at 5000rpm for 30min, a pre-emulsion is obtained; the pre-emulsion is transferred to a closed reactor, and n-dodecyl mercaptan and 2,2'-azobisisobutylamidine dihydrochloride are added, and nitrogen replacement is performed. Subsequently, the reaction is kept at 60°C for 5-8h under continuous stirring and nitrogen protection. After the reaction is completed, it is cooled to room temperature and filtered to obtain modified acrylic ester. In this step, the mechanical strength and durability of the acrylic emulsion are improved by adding modified nanoparticles.

[0051] S5. Preparation of self-bonding coating: 150 g of the modified epoxy resin emulsion prepared in step S2, 115 g of the modified acrylate emulsion prepared in step S4, and 8 g of polyethylene glycol ether are uniformly mixed, and stirred at a speed of 3000 rpm for 60 min to obtain a water-based self-bonding insulating coating for silicon steel.

[0052] Comparative Example 4: Except that 5 g of aluminum nitrate is not added in step S4, the remaining steps are the same as those in Example 3.

[0053] Comparative Example 5: Except that 6 g of silicon dioxide is not added in step S4, the remaining steps are the same as those in Example 3.

[0054] Figure 6 This is a TEM image of the boron-doped carbon fiber material prepared in Example 3 of the present invention. From the image, it can be seen that the boron-doped carbon fiber material prepared in the present invention still has a porous structure inside, indicating that the introduction of boron will not destroy the tubular structure of the carbon fiber material.

[0055] Example 4

[0056] S1. Soak 32g of melamine in 50mL of concentrated nitric acid and 20mL of concentrated sulfuric acid at 58°C. After soaking for 15h, wash with deionized water to obtain a white tubular sample. Mix the white powder sample and 2.5g of boric acid evenly, place it in a vacuum tube furnace, and vacuum calcine for 2.5h at a vacuum calcination temperature of 690°C. After vacuum carbonization, the white powder becomes a black tubular powder, which is a boron-doped carbon fiber material. Place the carbon fiber material in an acetone solution of γ-aminopropyltriethoxysilane (KH550) with a mass fraction of 1.8wt%. After ultrasonic treatment for 30min, centrifugal drying is performed to obtain a modified boron-doped carbon fiber. The introduction of boron in this step greatly improves the electronic structure of the carbon fiber surface, which is conducive to better dispersion of the carbon fiber in the coating. In addition, in this step, after the modified boron-doped carbon fiber is immersed in an acetone solution of γ-aminopropyltriethoxysilane (KH550), it can ensure that the carbon fiber is better immersed in the mixed resin system, thereby ensuring that the carbon fiber is fully impregnated.

[0057] S2, preparation of modified epoxy resin emulsion: weigh 110g of bisphenol A epoxy resin of model 6828 in a beaker, start stirring, stirring speed is 2000rpm, warm to 60℃; add 14g of modified boron-doped carbon fiber prepared in step S1 and 9g of hexadecyltrimethylammonium bromide (CTAB) after keeping warm for 13min, continue stirring for 28min; then drip 190g of deionized water into the beaker at a speed of 4g / min, and adjust the speed of the high-speed disperser to 5000rpm; after the dropwise addition is completed, reduce the dispersion speed to 2000rpm, keep the temperature at 65℃, keep warm for 1.5h, stir for 30min, cool to room temperature, filter and discharge, and obtain epoxy resin emulsion. Hexadecyltrimethylammonium bromide (CTAB) in this step is a cationic emulsifier, which can form stable micelles in aqueous solution and has good bactericidal properties. The interfacial adhesion between carbon fiber and polymer matrix plays a vital role in controlling the overall performance of the composite material. The interfacial adhesion of the modified boron-doped carbon fiber used in this step increases the structural integrity of the composite material and effectively transfers stress from the fiber to the matrix. The toughness of the coating is effectively improved by the epoxy resin and the modified boron-doped carbon fiber in this step.

[0058] S3, take 4g of aluminum nitrate, 5g of silicon dioxide and 1.5g of hexadecyltrimethylammonium bromide and add them to a 100mL reactor, then add 60mL of acetonitrile, react in a muffle furnace for 16h, the reaction temperature is 195℃; cool to room temperature and centrifuge to obtain black powder; place the black powder in a tubular furnace, in an Ar gas atmosphere, the reaction temperature is controlled at 580℃, and vacuum calcined for 2.6h to obtain modified nanoparticles. In this step, the acetonitrile solution is used to promote the coating of the carbon layer outside the silicon-aluminum nanoparticles, and the modified silicon-aluminum nanoparticles are obtained by vacuum calcination.

[0059] S4, prepare modified acrylic emulsion: 110g of octadecyl acrylate, 9g of acrylate-based silicone monomer, 4g of benzalkonium chloride (BAC), 2.5g of modified nanoparticles prepared in step S3, 40mL of propylene glycol, 75mL of deionized water and 19mL of glacial acetic acid are prepared and reacted in a constant temperature water bath for 68min, and the temperature is controlled at 60°C; then, after stirring at 5000rpm for 25min, a pre-emulsion is obtained; the pre-emulsion is transferred to a closed reactor, and n-dodecyl mercaptan and 2,2'-azobisisobutylamidine dihydrochloride are added, and nitrogen replacement is performed. Subsequently, the reaction is kept at 60°C for 6h under continuous stirring and nitrogen protection. After the reaction is completed, it is cooled to room temperature and filtered to obtain modified acrylic ester. In this step, the mechanical strength and durability of the acrylic emulsion are improved by adding modified nanoparticles.

[0060] S5. Preparation of self-bonding coating: 140 g of the modified epoxy resin emulsion prepared in step S2, 103 g of the modified acrylate emulsion prepared in step S4, and 7 g of polyethylene glycol ether are mixed evenly, and stirred at a speed of 3000 rpm for 50 min to obtain a water-based self-bonding insulating coating for silicon steel.

[0061] Comparative Example 6: Except that the modified epoxy resin emulsion is replaced by epoxy resin emulsion in step S5, the remaining steps are the same as those in Example 4.

[0062] Comparative Example 7: Except that the modified acrylate emulsion is replaced by acrylate emulsion in step S5, the remaining steps are the same as those in Example 4.

[0063] Peel strength test:

[0064] (1) Select a 25mm×100mm silicon steel sheet, clean the bonding surface of the silicon steel sheet, and ensure that there is no grease and impurities. Apply the water-based self-adhesive insulating coating evenly on one side of the silicon steel sheet. The coating thickness should be controlled to be 10-20μm. Align the silicon steel sheet coated with the coating prepared by the present invention with another silicon steel sheet, and apply a pressure of 0.8MPa to ensure that the coating is evenly distributed. Cure the silicon steel sheet at 120℃ for 1h.

[0065] (2) Fix the bonded sample on the peel tester, making sure that the bonding surface of the sample is at 90° to the loading direction. Apply the peel load and record the maximum peel force.

[0066] Calculate peel strength: Peel strength = maximum peel force / bonding length

[0067] The bonding length is 100 mm.

[0068] Table 1. Peel strength of materials prepared in Examples 1-4 and Comparative Examples 1-7 of the present invention

[0069] Peel strength N / cm Comparative Example 1 3.3±0.2 Comparative Example 2 3.8±0.1 Comparative Example 3 3.7±0.6 Comparative Example 4 3.9±0.2 Comparative Example 5 2.9±0.4 Comparative Example 6 2.7±0.1 Comparative Example 7 4.0±0.3 Example 1 7.5±0.4 Example 2 6.8±0.5 Example 3 7.6±0.3 Example 4 7.3±0.1

[0070] Analysis of the peel strength of the materials prepared in Comparative Examples 1 and 2 and Example 1 shows that the tubular material with a thinner diameter after treatment in Example 1 of the present invention can be better mixed with boric acid to prepare modified boron-doped carbon fibers that are better dispersed in the coating, which is beneficial to improving the bonding strength of the material. Comparison of the peel strength of the materials prepared in Comparative Examples 3 and Example 2 shows that the introduction of boron promotes the modification of carbon fibers and plays a positive role in improving the bonding of the materials. Comparison of the peel strength of the materials prepared in Comparative Examples 4 and 5 and Example 3 shows that there is a synergistic effect between silicon and aluminum in the modified nanoparticles. Only when silicon and aluminum exist at the same time, the bonding property of the prepared coating is the best. Comparison of the peel strength of the materials prepared in Comparative Examples 6 and 7 and Example 4 shows that the modification of the epoxy resin emulsion is beneficial to promoting the improvement of the bonding performance of the material.

[0071] The above-mentioned embodiments only express the specific implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the protection scope of the present invention. It should be pointed out that, for those skilled in the art, without departing from the concept of the present invention, any other changes, modifications, substitutions, combinations, simplifications made without departing from the spirit and principle of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.

Claims

1. A water-based self-adhesive insulating coating for silicon steel, characterized in that: The specific preparation steps include: S1. Soak 20-42g of melamine in 50mL of concentrated nitric acid and 20mL of concentrated sulfuric acid at a temperature of 55-60°C for 10-17h, then wash with deionized water to obtain a white tubular sample. Mix the white powder sample and 2-3g of boric acid evenly, place in a vacuum tube furnace, and calcine in vacuum for 2-3h at a temperature of 680-750°C. After vacuum carbonization, the white powder turns into a black tubular powder, which is a boron-doped carbon fiber material. Place the carbon fiber material in an acetone solution of γ-aminopropyltriethoxysilane, wherein the mass fraction of γ-aminopropyltriethoxysilane is 0.5-2.0wt%, and after ultrasonic treatment for 30min, centrifuge and dry to obtain a modified boron-doped carbon fiber. S2, preparation of modified epoxy resin emulsion: weigh 80-120g of bisphenol A epoxy resin of model 6828 into a beaker, start stirring at a stirring speed of 2000-3000rpm, and heat to a temperature of 55-66°C; after keeping warm for 10-15min, add 12-15g of modified boron-doped carbon fiber prepared in step S1 and 8-11g of hexadecyltrimethylammonium bromide, and continue stirring for 22-30min; then drip 150-230g of deionized water into the beaker at a speed of 3-5g / min, and adjust the speed of the high-speed disperser to 5000rpm; after the dropwise addition is completed, reduce the dispersion speed to 2000rpm, keep the temperature at 65°C, keep warm for 1-2h, then stir for 30min, cool to room temperature, filter and discharge, and obtain epoxy resin emulsion; S3, add 3-5g of aluminum nitrate, 4-6g of silicon dioxide and 1.5g of hexadecyltrimethylammonium bromide into a 100mL reactor, then add 60mL of acetonitrile, react in a muffle furnace for 12-18h, the reaction temperature is 180-220°C; cool to room temperature and centrifuge to obtain a black powder; place the black powder in a tubular furnace, in an Ar gas atmosphere, the reaction temperature is controlled at 550-680°C, and vacuum calcined for 2-3h to obtain modified nanoparticles; S4, preparing a modified acrylic emulsion: 80-130 g of octadecyl acrylate, 5-13 g of an acrylic ester-based silicone monomer, 3-5 g of benzalkonium chloride, 2-3 g of the modified nanoparticles prepared in step S3, 30-50 mL of propylene glycol, 60-80 mL of deionized water and 15-30 mL of glacial acetic acid are prepared and reacted in a constant temperature water bath for 50-80 min, and the temperature is controlled at 60° C.; then, the pre-emulsion is obtained after stirring at 5000 rpm for 20-30 min; the pre-emulsion is transferred to a closed reactor, n-dodecyl mercaptan and 2,2'-azobisisobutylamidine dihydrochloride are added, and nitrogen replacement is performed; then, the reaction is carried out at 60° C. for 5-8 h under continuous stirring and nitrogen protection; after the reaction is completed, the temperature is cooled to room temperature, and the modified acrylic emulsion is obtained after filtering; S5. Preparation of self-bonding coating: 110-150 g of the modified epoxy resin emulsion prepared in step S2, 90-115 g of the modified acrylate emulsion prepared in step S4, and 5-8 g of polyethylene glycol ether are uniformly mixed, and stirred at a speed of 3000 rpm for 40-60 min to obtain a water-based self-bonding insulating coating for silicon steel.

2. The water-based self-adhesive insulating coating for silicon steel according to claim 1, characterized in that: The steps In S1, 20 g of melamine is soaked in 50 mL of concentrated nitric acid and 20 mL of concentrated sulfuric acid, the temperature is controlled at 60°C, and after soaking for 10 hours, it is cleaned with deionized water to obtain a white tubular sample. The white powder sample and 3 g of boric acid are evenly mixed, placed in a vacuum tube furnace, and vacuum calcined for 3 hours at a vacuum calcination temperature of 680°C; after vacuum carbonization, the white powder becomes a black tubular powder, which is a boron-doped carbon fiber material; the carbon fiber material is placed in an acetone solution of γ-aminopropyltriethoxysilane, the mass fraction of γ-aminopropyltriethoxysilane is 0.5wt%, and after ultrasonic treatment for 30 minutes, centrifugal drying can obtain modified boron-doped carbon fiber.

3. The water-based self-adhesive insulating coating for silicon steel according to claim 1 or 2, characterized in that: In the step S1, 42 g of melamine is soaked in 50 mL of concentrated nitric acid and 20 mL of concentrated sulfuric acid, the temperature is controlled at 60° C., after soaking for 12 hours, it is cleaned with deionized water to obtain a white tubular sample, the white powder sample and 3 g of boric acid are evenly mixed, placed in a vacuum tube furnace, and vacuum calcined for 2 hours, and the vacuum calcination temperature is 690° C. After vacuum carbonization, the white powder becomes a black tubular powder, which is a boron-doped carbon fiber material; the carbon fiber material is placed in an acetone solution of γ-aminopropyltriethoxysilane, the mass fraction of γ-aminopropyltriethoxysilane is 1.5wt%, and after ultrasonic treatment for 30 minutes, centrifugal drying can obtain a modified boron-doped carbon fiber.

4. The water-based self-adhesive insulating coating for silicon steel according to claim 1, characterized in that: In the step S2, 80 g of bisphenol A epoxy resin of model 6828 is weighed into a beaker, and stirring is started at a speed of 2000 rpm, and the temperature is raised to 55° C.; after keeping warm for 10 minutes, 12 g of the modified boron-doped carbon fiber prepared in step S1 and 8 g of hexadecyltrimethylammonium bromide are added, and stirring is continued for 22 minutes; then 150 g of deionized water is dripped into the beaker at a speed of 3 g / min, and the speed of the high-speed disperser is adjusted to 5000 rpm; after the dripping is completed, the dispersion speed is reduced to 2000 rpm, the temperature is maintained at 65° C., and the temperature is kept warm for 1 hour, and then stirred for 30 minutes, cooled to room temperature, filtered and discharged, and the epoxy resin emulsion can be obtained.

5. The water-based self-adhesive insulating coating for silicon steel according to claim 1 or 4, characterized in that: In the step S2, 120 g of bisphenol A epoxy resin of model 6828 is weighed into a beaker, and stirring is started at a speed of 3000 rpm, and the temperature is raised to 66° C.; after keeping warm for 15 minutes, 15 g of the modified boron-doped carbon fiber prepared in step S1 and 11 g of hexadecyltrimethylammonium bromide are added, and stirring is continued for 30 minutes; then 230 g of deionized water is dripped into the beaker at a speed of 5 g / min, and the speed of the high-speed disperser is adjusted to 5000 rpm; after the dripping is completed, the dispersion speed is reduced to 2000 rpm, the temperature is maintained at 65° C., and the temperature is kept warm for 2 hours, and then stirred for 30 minutes, cooled to room temperature, filtered and discharged, and the epoxy resin emulsion can be obtained.

6. The water-based self-adhesive insulating coating for silicon steel according to claim 1, characterized in that: In the step S3, 3 g of aluminum nitrate, 4 g of silicon dioxide and 1.5 g of hexadecyltrimethylammonium bromide are added to a 100 mL reactor, and then 60 mL of acetonitrile is added, and the mixture is reacted in a muffle furnace for 12 h at a reaction temperature of 180° C.; after cooling to room temperature, the mixture is centrifuged and dried to obtain a black powder; the black powder is placed in a tubular furnace in an Ar gas atmosphere, the reaction temperature is controlled at 550° C., and vacuum calcined for 2 h to obtain modified nanoparticles.

7. The water-based self-adhesive insulating coating for silicon steel according to claim 1 or 6, characterized in that: In the step S3, 5 g of aluminum nitrate, 6 g of silicon dioxide and 1.5 g of hexadecyltrimethylammonium bromide are added to a 100 mL reactor, and then 60 mL of acetonitrile is added, and the mixture is reacted in a muffle furnace for 18 h at a reaction temperature of 220° C.; after cooling to room temperature, the mixture is centrifuged and dried to obtain a black powder; the black powder is placed in a tubular furnace in an Ar gas atmosphere, the reaction temperature is controlled at 680° C., and vacuum calcined for 3 h to obtain modified nanoparticles.

8. The water-based self-adhesive insulating coating for silicon steel according to claim 1, characterized in that: In the step S4, 80 g of octadecyl acrylate, 13 g of acrylate-based silicone monomer, 3 g of benzalkonium chloride, 3 g of modified nanoparticles prepared in step S3, 30 mL of propylene glycol, 60 mL of deionized water and 15 mL of glacial acetic acid are prepared and reacted in a constant temperature water bath for 80 min, and the temperature is controlled at 60° C.; then, the pre-emulsion is obtained after stirring at 5000 rpm for 20 min; the pre-emulsion is transferred to a closed reactor, and n-dodecyl mercaptan and 2,2'-azobisisobutylamidine dihydrochloride are added, and nitrogen replacement is performed; then, the reaction is carried out at 60° C. for 5 h under continuous stirring and nitrogen protection; after the reaction is completed, the temperature is cooled to room temperature, and the modified acrylate emulsion is obtained after filtering.

9. The water-based self-adhesive insulating coating for silicon steel according to claim 1, characterized in that: In the step S5, 110 g of the modified epoxy resin emulsion prepared in step S2, 115 g of the modified acrylate emulsion prepared in step S4, and 5 g of polyethylene glycol ether are uniformly mixed, and stirred at a speed of 3000 rpm for 40 minutes to obtain a water-based self-adhesive insulating coating for silicon steel.

10. A water-based self-adhesive insulating coating for silicon steel prepared according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Water-based double-component anticorrosive paint and preparation method thereof

    CN106833207A

  • Corrosion-resisting and high-strength waterborne epoxy resin coating

    CN107353779A

  • High-strength waterproof corrosion-resistant explosion-proof coating

    CN111500151A

  • Preparation method of graphene oxide / acrylate-epoxy resin composite anticorrosive paint

    CN111518450A

  • Preparation method of modified acrylate emulsion

    CN117069898A